Prevalence of medically induced psychological trauma and its influence on women's health. Issue 2 (13th February 2023) - Krolak, Monika; Hämmerli Keller, Katja; Schmidt, Roger; Nobel, Gloria; Germann, Nicolas; Schmid, Dagmar; Hornung, René
Abstract: Objective: The aim of the present study was three‐fold. One, to assess the prevalence of medical traumatization in outpatients of a gynecologic department; two, to analyze the relationship of medical traumatization with adverse childhood events; and three, to investigate the extent to which medical traumatization affects the health outcomes of woman. Methods: Between January and September 2022, a prospective cross‐sectional study recruited patients of a gynecologic outpatient clinic at St. Gallen Cantonal Hospital in Switzerland. Medical trauma was a self‐reported item. The presence of adverse childhood events was assessed using the Childhood Trauma Questionnaire. The severity of post‐traumatic stress was evaluated using the Impact of Event Scale Revised questionnaire. Results: In total, 227 patients were recruited. Medical trauma was reported by 20% of the interviewees and it was strongly associated with obesity ( A  = 0.005). Undergoing surgery was most commonly the source of psychological distress (5.7%) followed by delivery (4.8%), pregnancy loss (4.8%), and cancer diagnosis (4.0%). Yet, fewer than 1% of the patients reached the threshold suggesting post‐traumatic stress disorder. Conclusions: We found no relationship between the medical trauma, adverse childhood events, cardiovascular disease, or substance abuse. The presence of medical trauma was associated with the patient's body mass index (calculated as weight in kilograms divided by the square of height in meters). Synopsis: We found that one in five women in our population reported having a medical psychological trauma. Its presence was associated with the patient's BMI.